Gra z konwencją literatury dokumentu w powieści Hanny Sokołowskiej „Kosa, czyli ballada kryminalna o Nowej Hucie” - Mazurkiewicz, Adam (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
Looking for new sources of inspiration, authors of crime stories begin to combine literary fiction with historical facts. Thanks to that they create quasi-documentary narratives in which crime serves as a pretext to show historical settings (in Hanna Sokołowska’s novel the setting are the 1970s). This way the reader can be culturally embedded in “post-memory.”